In vivo expression of the HBZ gene of HTLV-1 correlates with proviral load, inflammatory markers and disease severity in HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP) - Saito, Mineki; Matsuzaki, Toshio; Satou, Yorifumi; Yasunaga, Jun-ichirou; Saito, Kousuke; Arimura, Kimiyoshi; Matsuoka, Masao; Ohara, Yoshiro (Retrovirology, 2009)
Recently, human T-cell leukemia virus type 1 (HTLV-1) basic leucine zipper factor (HBZ), encoded from a minus strand mRNA was discovered and was suggested to play an important role in adult T cell leukemia (ATL) development. However, there have been no reports on the role of HBZ in patients with HTLV-1 associated inflammatory diseases. We quantified the HBZ and tax mRNA expression levels in peripheral blood from 56 HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) patients, 10 ATL patients, 38 healthy asymptomatic carriers (HCs) and 20 normal uninfected controls, as well as human leukemic T-cell lines and HTLV-1-infected T-cell lines, and the data were correlated with clinical parameters. The spliced HBZ gene was transcribed in all HTLV-1-infected individuals examined, whereas tax mRNA was not transcribed in significant numbers of subjects in the same groups. Although the amount of HBZ mRNA expression was highest in ATL, medium in HAM/TSP, and lowest in HCs, with statistical significance, neither tax nor the HBZ mRNA expression per HTLV-1-infected cell differed significantly between each clinical group. The HTLV-1 HBZ, but not tax mRNA load, positively correlated with disease severity and with neopterin concentration in the cerebrospinal fluid of HAM/TSP patients. Furthermore, HBZ mRNA expression per HTLV-1-infected cell was decreased after successful immunomodulatory treatment for HAM/TSP. These findings suggest that in vivo expression of HBZ plays a role in HAM/TSP pathogenesis.